A Pragmatic Study of Verbal Irony in Selected Yoruba Home Videos - Dare, Samson Adeyeye; Sanni, Mumin Akinkunle (NIU Journal of Humanities; Vol 4 No 4 (2019): KIU Journal of Humanities, Vol. 4 No. 4, December 2019, 2020)
A considerable research has been devoted to verbal irony in Yoruba language in dramatic texts and other written texts but not much attention has been paid to verbal irony in Yoruba home videos. Hence this study examines verbal irony in selected Yoruba home videos using pragmatic theory. A total of ten home videos produced within the last ten years are randomly selected for analysis using the combined pragmatics theories of Cooperative Principle (CP) and â€œpragmemeâ€ proposed by Grice ((1975) and Mey (2001) respectively. The paper notes that socio-cultural background of the speaker and the listener contributes to the effective use of verbal irony. It notes, furthermore, that verbal irony is deployed to serve the purpose of instilling cultural value and norms in the Yoruba people including exposure to the supernatural world. Verbal irony is deployed in market places, homestead and public places. These discoveries will prepare the way for further studies in pragmatics and the peculiar linguistic behaviour of the Yoruba people. Other situational use of verbal irony could be investigated, as well as other linguistic functions of verbal irony in Yoruba language.  Keywords:  Verbal Irony, Pragmatics, Linguistic Functions, Home Video